Performance Analysis of Distance-Based Wireless Transceiver Placement for Wireless NoCs with Deterministic Routing - Asrani, Lit; Shamsiah, Suhaili; Nazreen, Junaidi; Shirley, Rufus; Nurul Izzati, Hashim (Electrical Engineering/Electronics, Computer, Communications and Information Technology Association (ECTI) of Thailand, 2024)
This research analyzes the impact of wireless transceiver subnet clustering on a hundred-core mesh-structured WiNoC architecture. The study aims to examine the effects of distance-based wireless transceiver placements on transmission delay, network throughput, and energy consumption in a mesh Wireless NoC architecture with a hundred cores, particularly under the X-Y, West-First, Negative-First, and North-Last routing strategies. This research investigates the impact of positioning radio subnets at the farthest, farther, nearest, and closest positions within an architecture featuring four wireless transceivers. The Noxim simulator was used to simulate the analyzed wireless transceiver placements on the hundred-core mesh-structured WiNoC designs, with the objective of validating the results. The architecture with the wireless transceiver positioned at the midway proximity (nearer and further) delivers the best performance, as evidenced by the lowest latencies for all evaluated deterministic routing algorithms, corresponding to the simulation outcomes.